The Construction and Exploration of Spatial Narrative under the Ken of Metaverse - Duan, Xiaoxiao; Chen, Caiying (Journal of Intelligent Communication, 2022)
With the continuous development and mutual construction of digital technology and the concept of the metaverse, the expression paradigm formed in the evolution of the metaverse will be established in continuous replacement. Based on current spatial construction process of metaverse, the characteristics and advantages of traditional spatial narrative will provide theoretical basis and basic rules for the construction of the metaverse expression paradigm. Simultaneously, the emergence of digital space will continually expand the concept of spatial narrative. This paper argues that the “great time” theory in spatial narrative will have positive effects in the spatial construction of metaverse and contribute to the expression of relevant rules of metaverse paradigm.